FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKTAATAN DIET PADA PASIEN DIABETES MELITUS DI RUMAH SAKIT ROEMANI SEMARANG (STUDI : FENOMENOLOGI) - Retnaningsih, Dwi (Jurnal Ilmu dan Teknologi Kesehatan, 2010)
Result of newest research report that DM is not only caused by calm factor like estimed previously by many people but DM is also influenced by habit of environment and life pursuant. Based on observation and interview, some patients whose suffering DM find difficulties in conducting diet and will till now, there is no drug capable to heal DM. Four step management of diabetes agreed on all expert are education, diet planning, exercise, and farmacology intervention. The most component often generate the problem of at patient DM is adherence of arrangement or diet. But, in reality patient of DM a lot take no account of his diet. The goal this research is to know factors which cause difficulty in the DM patient in Roemani at Semarang. This Research represent reseach qualitative study of fenomenology. Execution of research used of observation and interview guidance. After research done, to be obtained by result of factors causing disobedience of dietÂ  at DM patient in Roemani Hospital at Semarang are boredom, feeling, knowledge, environmental and habit and life style factors.Â